Impact of Baseline Central Retinal Thickness on Outcomes in the VIVID-DME and VISTA-DME Studies - Edoardo Midena; Mark Gillies; Todd A. Katz; Carola Metzig; Chengxing Lu; Yuichiro Ogura (Journal of Ophthalmology)
Purpose. To report the impact of baseline central retinal thickness (CRT) on outcomes in patients with diabetic macular edema (DME) in VIVID-DME and VISTA-DME. Methods. Post hoc analyses of two randomized controlled trials in which 862 DME patients were randomized 1 : 1 : 1 to treatment with intravitreal aflibercept 2.0 mg every 4 weeks (2q4), intravitreal aflibercept 2.0 mg every 8 weeks after five initial monthly doses (2q8), or macular laser photocoagulation at baseline and as needed. We compared visual and anatomical outcomes in subgroups of patients with baseline CRT < 400 μm and ≥400 μm. Results. At weeks 52 and 100, outcomes with intravitreal aflibercept 2q4 and 2q8 were superior to those in laser control-treated patients regardless of baseline CRT. When looked at in a binary fashion, the treatment effect of intravitreal aflibercept versus laser was not significantly better in the ≥400 μm than the <400 μm group; when looked at as a continuous variable, baseline CRT seemed to have an impact on the treatment effect of intravitreal aflibercept versus laser. Conclusions. Post hoc analyses of VIVID-DME and VISTA-DME demonstrated the benefits of intravitreal aflibercept treatment in DME patients with baseline CRT < 400 μm and ≥400 μm. This trial is registered with NCT01331681 and NCT01363440.